PELECEHAN SEKSUAL ANTAR ANAK DALAM PERSPEKTIF HUKUM PIDANA - Ladin, L. (IAIN Tulungagung, 2016)
Decency crime in general is an act or acts of violating decency orimmoral intentionally damaging public decency or others is notvolition, the victim, by force and by threats of violence. Laws threatenpunishment for anyone who violates the act. Meanwhile, the intendedpublic is for example in school buildings, a bunch of people, places thatcan circulate to each person, and so on. Through a variety of mediacan be seen almost every day crimes with various kinds. Similarly,the perpetrators themselves, anyone can be a perpetrator of a crime,whether the perpetrators are still children, older people, both men andwomen. So regardless of age or gender, although in reality the numberof crimes committed by children is relatively small, but it cannot bedenied that the crimes committed by these children happen everywhere.As crime decency committed by minors, it is certainly influencedby many factors, among others, because the child does not receiveaffection from their parents, parents forget themselves as parents beingtoo busy, also caused by certain parties that is not responsible for, theinfluence of the environment, freedom of association as a result of notgetting attention from their parents at home, their freelance film andvideo sensors, readings can damage the child’s psyche.Kata kunci: Pelecehan Seksual, Anak, Tinjauan Hukum Pidana